2015
DOI: 10.15252/embj.201591382
|View full text |Cite
|
Sign up to set email alerts
|

The tRNA methyltransferase Dnmt2 is required for accurate polypeptide synthesis during haematopoiesis

Abstract: The Dnmt2 enzyme utilizes the catalytic mechanism of eukaryotic DNA methyltransferases to methylate several tRNAs at cytosine 38. Dnmt2 mutant mice, flies, and plants were reported to be viable and fertile, and the biological function of Dnmt2 has remained elusive. Here, we show that endochondral ossification is delayed in newborn Dnmt2-deficient mice, which is accompanied by a reduction of the haematopoietic stem and progenitor cell population and a cell-autonomous defect in their differentiation. RNA bisulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
183
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(190 citation statements)
references
References 46 publications
5
183
0
2
Order By: Relevance
“…RNA modifications are particularly enriched in tRNAs, where they are often linked to translational regulation (Agris 2008). In this context, it has been shown that m5C modification of tRNA plays an important role in tRNA stability and in the regulation of translational fidelity (Schaefer et al 2010;Tuorto et al 2012Tuorto et al , 2015. Furthermore, m5C is also a widely conserved modification of rRNA, where it is implied in the quality control of ribosome biogenesis (Sharma et al 2013;Bourgeois et al 2015;Schosserer et al 2015).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…RNA modifications are particularly enriched in tRNAs, where they are often linked to translational regulation (Agris 2008). In this context, it has been shown that m5C modification of tRNA plays an important role in tRNA stability and in the regulation of translational fidelity (Schaefer et al 2010;Tuorto et al 2012Tuorto et al , 2015. Furthermore, m5C is also a widely conserved modification of rRNA, where it is implied in the quality control of ribosome biogenesis (Sharma et al 2013;Bourgeois et al 2015;Schosserer et al 2015).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…In mammals, deposition of m 5 C by DNMT2 or NSUN2 protects tRNAs from endonucleolytic cleavage by preventing binding of the endonuclease angiogenin and cleavage into two small non-coding RNA fragments (Fig. 5A,B) (Blanco et al, 2014;Schaefer et al, 2010;Tuorto et al, 2015). Lack of NSUN2-mediated methylation causes accumulation of 5′ tRNA-derived fragments and decreases global protein translation in cells (Blanco et al, , 2014.…”
Section: Mechanism Of Action Of Cytosine-5 Methylationmentioning
confidence: 99%
“…By contrast, loss of DNMT2-mediated methylation of tRNA Asp GTC , Gly GCC and Val AAC causes tRNA-specific fragmentation patterns, which leads to specific codon mistranslation (Fig. 5A,B) (Tuorto et al, 2015). Cytosine-5 methylation of vault non-coding RNAs alters their processing into Argonaute-associated small RNA fragments that can function as miRNAs and regulate the translation of targeted mRNAs (Fig.…”
Section: Mechanism Of Action Of Cytosine-5 Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The family of mammalian methyltransferases consists of five enzymes, of which three possess enzymatic activity for DNA methylation -the remaining member of the group, DNMT2 plays an important role in polypeptide synthesis through tRNA methylation, hence its alternative name: TRDMT1 (tRNA aspartic acid methyltransferase 1) [6].…”
Section: Introductionmentioning
confidence: 99%